Automated Handling Product Shelving and Checkout Application Management System - HALID, NURUL ATHIRAH (Multidisciplinary Applied Research and Innovation, 2023)
Automated Handling Product Shelving and Checkout Application Management System is an automatic guide vehicle that carries goods in and out of the warehouse in addition to warehouse inventory management system that aims to make the inventory management system to be more effective. Incoming and outgoing goods transfer is handled by an automated guided vehicles(AGVs). AGVs play a significant role in the efficient and accurate distribution of commodities and the movement of materials. AGVs route planning has made great achievements in warehouse management. It is simple to track the merchandise in the warehouse using an efficient inventory management system. An organised fulfilment centre results from an effective inventory management approach. More effective current and upcoming fulfilment strategies are produced by a well-organized warehouse. As software and sensor technology has advanced, AGV systems' capabilities have exponentially increased. Particularly, a number of technologies might have a significant influence on the AGV market. Cameras may enhance pallet detection in the future, enabling cars to communicate with manual trucks more successfully. Additionally, this technology may make standalone cars run more effectively inside of buildings. . The methodology that has been used to develop this system working on employs agile approach, with the primary goal of identifying flaws in the development process. This study reviews the literature on AGV system design and control in production, distribution, transhipment, and transportation. Also, we provide a more specialized research approach in the design and control of AGV systems and inventory management systems.